Synthesis, Characterization and Antimicrobial Screening of Cobalt(II), Nickel(II) and Copper(II) Complexes with Schiff Base Derived from 2-Aroyl Quinoxaline Semicarbazone - Rai, B.K. (Asian Journal of Chemistry, 2010)
Complexes of general formula [M(AQSC)2X2], where M = cobalt(II), nickel(II) and copper(II), AQSC = 2-aroyl quinoxaline semicarbazone, X = Cl–, Br–, I–, NO3– and ClO4– have been prepared. Complexes were characterized by analytical analyses and physico-chemical methods. The ligand, 2-aroyl quinoxaline semicarbazone behaves as a neutral, bidentate chelateing agent and bonded to the metal ion through azomethine nitrogen and oxygen atom of semicarbazone moiety. The remaining coordinating sites are occupied by anions such as Cl–, Br–, I–, NO3– and ClO4–. Electronic spectra and magnetic susceptibility measurements reveal octahedral geometry. The complexes were found to be non-electrolytic in nature on the basis of low value of molar conductance. The ligand as well as metal complexes have been screened for their antibacterial and antifungal activity.